2005
DOI: 10.1111/j.1524-6175.2004.04463.x
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Alcohol Consumption and Hypertension: Clinical Implications of Current Research

Abstract: Substantial evidence demonstrates that: 1) heavy alcohol consumption (three or more standard drinks per day) is associated with and predictive of hypertension; 2) reduction in alcohol consumption is associated withA s the most common primary diagnosis in the United States, hypertension affects approximately 30% of the population and more than one half of people over the age of 60.1,2 An additional 22% may be prehypertensive. Hypertension is the leading cause of stroke and congestive heart failure and the secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 44 publications
3
33
0
4
Order By: Relevance
“…Studies have shown an association between alcohol ingestion and blood pressure [29]. We did not perform a systematic investigation of alcohol consumption in our study.…”
Section: Discussionmentioning
confidence: 90%
“…Studies have shown an association between alcohol ingestion and blood pressure [29]. We did not perform a systematic investigation of alcohol consumption in our study.…”
Section: Discussionmentioning
confidence: 90%
“…Excessive alcohol consumption is also reported to be associated with hypertension. On this basis, the determination of CDT has been proposed as feedback of alcohol abuse in patients treated for Type 2 diabetes and hypertension [68,69].…”
Section: Clinical Use Of Cdtmentioning
confidence: 99%
“…Several reports highlight the value of PEth for identification of harmful drinking (Aradottir et al, 2006, Hahn et al, 2010, Hansson et al, 1997, Miller et al, 2005, Stewart et al, 2010, Hahn et al, 2012), monitoring consumption during treatment (Kip et al, 2008), and various forensic applications (Marques et al, 2011, Marques et al, 2010). Yet a more complete characterization of the synthesis and elimination of PEth would provide more accurate estimations of the amount and time frame of ethanol consumption.…”
Section: Introductionmentioning
confidence: 99%